Return to the 1960s: the Role of ‘68 in Paul Auster’s Life and Work - Jesper Præst Nielsen (Revue LISA)
This essay explores the impact of 1968 on Paul Auster’s life and work. Its main analytical focus is on Auster’s critique of the anti-authoritative ethos of his generation in the early fictional autobiography Moon Palace (1989), but it draws comparisons to his later work as well, including 4 3 2 1 (2017) and the autobiographies Hand to Mouth (1997) and Report from the Interior (2013). Auster’s participation in the 1968 student uprising and his subsequent witnessing of the radicalization of the student movement have resulted in an authorial stance on ’68 that is marked by ambivalence and hindsight bias. Auster’s early letters show that Auster subscribed to a Marxist worldview before ’68, that his experiences in April changed him, and that he has since assumed center-left position in his prose work. Originally founded on Merleau-Ponty’s post-Cartesian philosophy, this position enables Auster to remain sympathetic to the egalitarian and antiwar causes of the Left, but critical of the general rejection of authorities that so characterized the late 1960s. The essay concludes that Moon Palace can be read as an appeal for the depolarization of the American political past.